2006
DOI: 10.1098/rspb.2006.3480
|View full text |Cite
|
Sign up to set email alerts
|

Senescent birds redouble reproductive effort when ill: confirmation of the terminal investment hypothesis

Abstract: This study reports an experimental confirmation of the terminal investment hypothesis, a longstanding theoretical idea that animals should increase their reproductive effort as they age and their prospects for survival and reproduction decline. Previous correlational and experimental attempts to test this hypothesis have yielded contradictory results. In the blue-footed booby, Sula nebouxii, a long-lived bird, after initial increase, male reproductive success declines progressively with age. Before laying, mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
252
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(263 citation statements)
references
References 46 publications
(85 reference statements)
7
252
2
2
Order By: Relevance
“…These two colonies are in separate oceanographic habitat regions of the archipelago, but exhibit similar breeding histories, suggesting the possibility that breeding has been poor across the archipelago since 1997 and depends little on spatial habitat variation. If so, then the age structure of the current population must be strongly biased toward elderly individuals; if Blue-footed Boobies show actuarial senescence, as Nazca Boobies do (Anderson and Apanius 2003) in addition to reproductive senescence (Velando et al 2006), then the birth and death processes leading to smaller population size can be expected to accelerate in the future.…”
Section: Discussionmentioning
confidence: 99%
“…These two colonies are in separate oceanographic habitat regions of the archipelago, but exhibit similar breeding histories, suggesting the possibility that breeding has been poor across the archipelago since 1997 and depends little on spatial habitat variation. If so, then the age structure of the current population must be strongly biased toward elderly individuals; if Blue-footed Boobies show actuarial senescence, as Nazca Boobies do (Anderson and Apanius 2003) in addition to reproductive senescence (Velando et al 2006), then the birth and death processes leading to smaller population size can be expected to accelerate in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Terminal investment has been empirically documented in other systems. For example, house sparrows injected with Paramyxo virus vaccine were more likely to lay a second clutch in a single season (Bonneaud et al 2004), male blue-footed boobies treated with liposaccharides to elicit an immune response had increased reproductive success (Velando et al 2006), and Tasmanian devil populations afflicted with devil facial tumor disease showed precocial reproduction (Jones et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Extrapair sires are predominantly older males (Wetton et al 1991;Cleasby and Nakagawa 2012;Hsu et al 2015), which could mean that correlated differences in parental investment between males with and without EPP could indirectly be driven by male age. Several studies have shown that older males are better at obtaining EPPs and also invest more into paternal care than younger males (Kempenaers and Sheldon 1997;Houston and McNamara 2002;Velando et al 2006;Hammers et al 2012). Thus, age alone as a flexible male state might potentially drive any association between paternal care and paternity.…”
Section: The Problemmentioning
confidence: 99%